The Eastern Partnership and its Impact on Self-Governance Reform in Ukraine - Vadym Zheltovskyy (CES Working Papers, 2016)
Article poses a question on the effectiveness of the European policy for Eastern Partnership in Ukraine under current circumstances of political and military crisis. Particularly, the role of Poland as a key country for the success of given policy in Ukraine is taken into consideration with the emphasis on Polish-Ukrainian cooperation on the issue of self-governance reform in Ukraine. The aim of the article is threefold. First, to analyse the main trends of EU-Ukraine cooperation in terms of the EaP policy. Second, to present author's research on the role of different political and social actors from Poland and Ukraine (local authorities, non-governmental organizations, Academia) in implementation of European experience on self-governance reform and decentralization processes on Ukrainian ground. Finally, the article makes an attempt to evaluate the EU strategy in regard to Ukraine and present possible ways for further cooperation as regards the reform of self-governance in Ukraine.
Keywords: 330; European policy for Eastern Partnership; self-governance; decentralization